Polyvinylpyrrolidone (PVP)-Assisted Solvothermal Synthesis of Mesoporous TiO2 Nanoparticles as an Active Material for Enzymatic Electrochemical Glucose Sensor. Issue 11 (2nd November 2021) - Amri, Fauzan; Bonardo, Doli; Rezki, Muhammad; Septiani, Ni Luh Wulan; Iqbal, Muhammad; Syarif, Dani Gustaman; Nugraha,; Yuliarto, Brian
Abstract : This study reports on an enzymatic glucose sensor based on mesoporous TiO2 nanoparticles (MTNPs) synthesized by a simple solvothermal method. The unique structure of MTNPs with a fairly homogenous shape, porous, and high crystallinity is the consequence of the use of PVP yang during the synthesis process. PVP plays an important role in creating the uniform morphology and mesoporous structure of MTNPs-2. The success of glucose oxidase immobilization on the surface of MTNPs was proven by FTIR and UV–vis characterizations. The prepared GCE/MTNPs-2/GOx electrode successfully detects glucose molecules with good sensing performance with a sensitivity of 0.4098 μ A mM −1 cm −2, a wide linear range of 0.1–1 mM, and a relatively low detection limit of 73 μ M.